Caminhos feitos de água, conhecimento e cidadania: educação em ciências numa escola ribeirinha - SILVEIRA, Mara Rubia Ribeiro Diniz (Universidade Federal do Pará, 2012)
This work tells the practical research developed on the pedagogical one of education in sciences lived and constructed together with operating educators in the basic education of the School They are São José of a riverside, situated community in the Ilha Grande in the city of Belém. With the intention to know to understand practical the pedagogical one of these riverside educators, searching a link it enters the education in sciences and social-cultural practical daily of that community in view of possible interactions and studies of social subjects in the sciences of teaching. It was broken of fidgets, such as: how are configured practical the pedagogical ones that the professors of the School São José, come constructing, with respect to the socialcultural questions of the community of the Ilha Grande, in the production of the pertaining to school knowledge in the education in sciences of riverside children? The methodological option of inquiry was the participant research, when searching a investigation way that was not solitary, but yes, in company of the participants in the effort of together learning, to create in a dialogic and humanizante process. It is distinguished boarding narrative as form to ahead express the understanding and possible answers to the questionings of the experiences, learnings and listening of the happened voices of the research process. I conduced Half-structuralized interviews, and pedagogical meeting for study and plan with the teachers in the proposal of activities on socially significant subjects, in the area of the education in sciences. Of the moments of interviews, they had been constructed given that they make possible the emergency of subjects in relation to the school and the education of sciences, practical and conceptions of those riverside educators, such as: what think about the teachers the respect of the education of sciences, the place of the social-cultural questions in this education, and the affectivity as peculiarity in that riverside school. It was approached thematic: The açaizeiro - palm life source. The constructed data and the story from this boarding had been organized in form of thematic axles, which if constitute clippings of the experiences lived in the pedagogical meeting, in which if they detach relations of practical the pedagogical one of the riverside educators with the social-cultural questions of the community of the Ilha Grande. Practical pedagogical already existing, others that had been being constructed in walking of a proposal/bet of education in sciences. The analyses make possible to know and to understand practical the pedagogical in three dimensions: Practical near; Practical reconcile and Practical constructors. In way that in the interaction with the citizens they had provided to emerge (reverse speed) conciliations, to assume uncompleted and to perceive in transition when teaching sciences, having as thematic starting point a social-cultural one of that community.